2018
DOI: 10.3389/fmicb.2018.00654
|View full text |Cite
|
Sign up to set email alerts
|

The Fusarium graminearum Histone Acetyltransferases Are Important for Morphogenesis, DON Biosynthesis, and Pathogenicity

Abstract: Post-translational modifications of chromatin structure by histone acetyltransferase (HATs) play a central role in the regulation of gene expression and various biological processes in eukaryotes. Although HAT genes have been studied in many fungi, few of them have been functionally characterized. In this study, we identified and characterized four putative HATs (FgGCN5, FgRTT109, FgSAS2, FgSAS3) in the plant pathogenic ascomycete Fusarium graminearum, the causal agent of Fusarium head blight of wheat and barl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 91 publications
14
77
0
1
Order By: Relevance
“…HosA might directly deacetylate specific lysines on histones H3 and H4, repressing transcription of the respective gene-region, as shown for instance for orsellinic acid and aspercryptin cluster genes ( Figure 6 ). Indeed, it has been demonstrated for the orsellinic acid cluster that H3K9 acetylation, mediated by the Saga/Ada complex, might trigger its activation ( Nützmann et al, 2011 ) and a recent publication reports on two HATs of the plant pathogenic fungus Fusarium graminearum required for the regulation of secondary metabolism via acetylation of several lysine residues of H3 ( Kong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…HosA might directly deacetylate specific lysines on histones H3 and H4, repressing transcription of the respective gene-region, as shown for instance for orsellinic acid and aspercryptin cluster genes ( Figure 6 ). Indeed, it has been demonstrated for the orsellinic acid cluster that H3K9 acetylation, mediated by the Saga/Ada complex, might trigger its activation ( Nützmann et al, 2011 ) and a recent publication reports on two HATs of the plant pathogenic fungus Fusarium graminearum required for the regulation of secondary metabolism via acetylation of several lysine residues of H3 ( Kong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genes and gene regulators such as signaling proteins and transcription factors (TFs) are interconnected in GRNs. Many studies have attempted to dissect GRNs using a reductionist approach by analyzing the gene expression profiles of Fg mutants [9][10][11]. Though conceptually valid, this approach is time-consuming and unrealistic as a method of decoding the highly complex GRNs of eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…All known bacterial KATs that have been discovered to date belong to the Gcn5-related N-acetyltransferase family; fewer deacetylases are encoded by prokaryotes, which means that acetylation and deacetylation processes in fungi are more complex with a higher proportion of acetylated proteins in eukaryotes ( Tables 1 , 2 ; Hentchel and Escalante-Semerena, 2015 ). KATs play a vital role in the morphogenetic hyphae growth, biofilm formation, drug resistance, and virulence ( Kong et al, 2018 ; Lin et al, 2020 ). In B. bassiana , deletion of g cn5 led to severe defects in colony growth and loss of cuticle infection ( Cai et al, 2018b ).…”
Section: Role Of Acetylation/deacetylation In Fungal Virulencementioning
confidence: 99%
“…Hyphae have a strong ability to adhere and invade the host, making it easy to maintain their colonization and escape attacks from the host immune system, probably through the release of cell type-specific virulence factors, such as adhesins (e.g., Hwp1, Als3, Als10, Fav2, and Pga55), tissue-degrading enzymes (e.g., Sap4, Sap5, and Sap6), and antioxidant defense proteins (e.g., Sod5) ( Sudbery, 2011 ; Noble et al, 2017 ). Acetylation and deacetylation play critical regulatory roles in regulating the initiation and maintenance of hyphal development ( Garnaud et al, 2016 ; Kong et al, 2018 ; Lee et al, 2019 ). Tribus et al (2010) found that the repression of the promoter of rpdA knockdown strains resulted in distorted and hyperbranched hyphae and a tremendous loss of radial growth of fungal colonies.…”
Section: Role Of Acetylation/deacetylation In Fungal Virulencementioning
confidence: 99%
See 1 more Smart Citation